Adverse changes in close social ties reduce fruit and vegetable intake in aging adults: a prospective gender-sensitive study of the Canadian longitudinal study on aging (CLSA) - Sanaz Mehranfar; Gilciane Ceolin; Rana Madani Civi; Heather Keller; Rachel A. Murphy; Tamara R. Cohen; Annalijn I. Conklin (International Journal of Behavioral Nutrition and Physical Activity)
Abstract Background Close social ties are known to increase survival, reduce chronic diseases, and promote healthful eating. Little research has explored whether adverse changes in these relationships lead to less healthful eating in older adults, with attention to gender differences. Methods Prospective study using 3 waves of the Canadian Longitudinal Study on Aging (CLSA) in a sample of middle-age and older adults (45–85 y) reporting daily intake of fruit or vegetable (F/V) intake (at least one time per day) at baseline using dietary data collected by CLSA’s Short Diet Questionnaire. We used multivariable multilevel logistic regression with interaction terms (social tie x gender) to determine whether adverse changes in close social ties (marital status and living arrangement) between baseline (2011–2015) and follow-up 1 (2015–2018) led to developing less healthful eating measured by non-daily intake of F/V at follow-up 2 (2018–2021) (n = 15,672); models adjusted for biological, behavioural, socioeconomic, and socio-political confounders. Results Distinct transitions by gender precipitated a change from daily F/V intake (healthful eating) to less frequent intakes (unhealthful eating). Compared to women remaining partnered, women remaining non-partnered over 3 years had 21% higher odds of reducing healthful intake of vegetables at 6-year follow-up (OR 1.21 [95% CI: 1.07, 1.38]). Becoming divorced increased the odds of reducing healthful intake of fruits among women (1.76 [1.16, 2.66]) compared to referent. Women remaining lone-living were less likely to reduce healthful fruit intake (0.86 [0.74, 0.99]), compared to remaining co-living. Compared to men remaining partnered, men who became divorced or widowed had 91% greater odds of reducing healthful vegetable intake (1.91 [1.25, 2.92] and 1.91 [1.17, 3.13], respectively). Men who remained non-partnered or became widowed were also more likely to reduce healthful fruit intake (1.20 [1.03, 1.41] and 1.99 [1.26, 3.15], respectively), compared to referent. Finally, men who became lone-living and co-living were more likely to reduce healthful intakes of vegetables (1.42 [1.06, 1.91] and 1.55 [1.04, 2.32]) and fruits (1.48 [1.11, 1.96] and 1.48 [1.00, 2.18]), compared to men remaining co-living. Conclusions Findings showed that adverse changes in close social ties led to the development of less healthful eating among aging adults in Canada, and these prospective associations appeared to be gendered. Public health and nutrition interventions should consider the social context as a risk factor to address gender disparities in food intake in the aging population.